Impact Localization of Thin Plate Structures Using Pzt-Array Based Passive Wave Method. (May 2019) - Yan, S.; Li, B.W.
Abstract: Impact of foreign objects is one of the main reasons for the damage of thin plate structures, resulting in property losses or unexpected accidents. Therefore, a rapid and effective impact localization of thin plate structures is of great value. In this paper, a localization method is proposed based on the passive wave method, aiming at locating the impact quickly and accurately. First, a square PZT array composed of 4 PZT sensors was designed, and a hyperbolic localization algorithm was derived according to time-different of arrival (TDoA) for different sensors in the array. Then, Matlab calculation software was used to perform DB wavelet decomposition on impact signals, the time delay was calculated by Lamb wave of A0 mode in D5 detail signals, and the velocity of A0 mode wave was determined by the dispersion curve for 1 mm thick aluminum plate. Finally, the impact point was located to experimentally verify the effectiveness of the proposed localization method. Experimental results show that the hyperbolic positioning algorithm based on TDoA can accurately identify impact locations, and wavelet decomposition can effectively identify single mode Lamb waves. The proposed method has the characteristics of fastness and accuracy, which is suitable for single object impact localization on thin plate structures.